Pengaruh Work-life balance Terhadap Retensi Karyawan Dengan Moderasi Kompensasi Di PT Sucofindo Cabang Utama Surabaya - Putri, Savega Novialdi Pratama; Rozaq, Khoirur (Jurnal Ilmu Manajemen, 2025)
This study aims to analyse the effect of work–life balance on employee retention with the moderation of compensation. This study applied a quantitative approach. The data collection technique used was the saturated sample technique. The total number of respondents was 99, obtained by distributing questionnaires directly. This study uses a Partial Least Square–Structural Equation Model (PLS–SEM) analysis technique. The results found that work–life balance has no significant effect on employee retention. Compensation has a significant positive effect on employee retention. Meanwhile, the moderation test could not be carried out further because the influence of work–life balance on employee retention was proven to have no effect This study suggests that while work–life balance policies are often considered important in employee retention, they may not be the primary determinant. Instead, companies should prioritise other factors, such as compensation, to enhance workforce loyalty effectively. The findings indicate that a well–structured compensation package, such as one encompassing salary, incentives, and benefits, plays a crucial role in reducing turnover. As a result, organissations aiming to improve employee commitment should focus on competitive compensation strategies as a central component of their retention efforts.